2016
DOI: 10.1108/jeim-04-2015-0034
|View full text |Cite
|
Sign up to set email alerts
|

A multi-analytical approach to understand and predict the mobile commerce adoption

Abstract: Purpose – The advent of mobile telephony devices with strong internet capabilities has laid the foundation for mobile commerce (m-commerce) services. The purpose of this paper is to empirically examine predictors of m-commerce adoption using a modification of the widely used technology acceptance model and the unified theory of acceptance and use of technology model. Design/methodology/approach – The data were collected from 213 responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
130
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 50 publications
14
130
3
4
Order By: Relevance
“…Trust is an important factor affecting adoption of technology (Yadav et al, 2016;Tarhini et al, 2016;Abbasi et al, 2015). As cloud computing services are relatively new concept among internet service integrity aspects of this technology needs to be explored.…”
Section: Trust and Behavioral Intention To Use Cloud Computingmentioning
confidence: 99%
“…Trust is an important factor affecting adoption of technology (Yadav et al, 2016;Tarhini et al, 2016;Abbasi et al, 2015). As cloud computing services are relatively new concept among internet service integrity aspects of this technology needs to be explored.…”
Section: Trust and Behavioral Intention To Use Cloud Computingmentioning
confidence: 99%
“…The First hypothesis (H1) which states a positive relationship between perceived usefulness and mobile commerce adoption was supported. Previous studies have equally proved that perceived usefulness is an important factor that can accelerate the rate of adoption of IS/IT such as mobile commerce Yadav et al, 2016), e-commerce (Guriting & Ndubisi, 2006;Jahangir & Begum, 2008) and e-banking (Aboelmaged & Gebba, 2013;Tan et al, 2010). These findings have shown that the adoption of mobile technology is majorly anchored on the perception of usefulness by the consumers as the consumers would only increase the rate of usage if, for instance, they can retrieve required information with urgency, perform the transaction seamlessly and achieve their daily and other mobile commerce transaction objectives ).…”
Section: Discussionmentioning
confidence: 99%
“…Succinctly, this study defines PU as the benefits which users of mobile commerce may derive from the usage of the m-commerce. Such benefits or values may include facilitation of the process in locating a store, purchasing/selling of services and products, paying utility bills, executing banking transactions and even joining social networks (Khalifa & Shen, 2008;Nassuora, 2013;Hsu & Wang, 2011;Hanafizadeh et al, 2014;Yadav et al, 2016). Without these values, users will not be willing to adopt information system like m-commerce while the objectives of expending huge amount on m-commerce facilities may not be achieved by the service providers (Pikkarainen et al, 2004).…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
See 1 more Smart Citation
“…Firms adapting social responsibility concept are gaining a large amount of power to affect the consumer brand perception (Almajali et al, 2016;Yadav et al, 2016), as cause-related marketing (C-RM) is subsumed under corporate social responsibility (CSR); in practice CSR and C-RM can serve as different public relations instruments. On the other hand, Che'ron et al (2012) show that C-RM has a positive effect on consumer attitudes and can be more efficient cost-wise.…”
Section: Introductionmentioning
confidence: 99%